Plasma apixaban levels in Chinese patients with chronic kidney disease—Relationship with renal function and bleeding complications - Sin, Chun-fung; Wong, Ka-ping; Wong, Tsz-fu; Siu, Chung-wah; Yap, Desmond Y. H. (Frontiers in Pharmacology, 2022)
Introduction Accumulation of apixaban in plasma is a major concern in patients with chronic kidney disease (CKD). Studies that investigated plasma apixaban level in CKD patients and its association with clinically significant events are scarce. Method Patients with CKD Stage 1 to 4 who were taking apixaban, either 2.5 mg BD or 5 mg BD were recruited. The peak and trough plasma apixaban level were measured after 2 hours and 12 hours of last dose respectively. The results were correlated with renal function and clinical events during the period of follow-up from 1 January 2018 to 31 October 2021. Results: 141 patients (CKD Stage 1, n = 12; Stage 2, n = 74; Stage 3, n = 48, stage 4, n =7) were included for analysis. The plasma peak and trough apixaban were significantly higher in patients with CKD stage 3 when compared with those having CKD stage 2 and 1 (peak levels: 223.4±107.8 ng/ml vs. 161.0±55.2 ng/ml vs. 126.6±30.2 ng/ml; trough levels: 118.3±67.9 ng/ml vs. 81.2±33.0 ng/ml vs. 51.9±31.1 ng/ml, p <0.05 or all) in patients taking 5 mg BD. Plasma trough apixaban level was negatively correlated with eGFR in patients taking 5mg BD (r2 = -0.174, p <0.001) and 2.5mg BD (r2 = -0.215, p <0.05). The plasma peak and trough apixaban level correlated with PT (r2= 0.065, p = 0.003 and r2=0.096, p<0.01 respectively). Multivariate analysis showed that plasma trough apixaban levels were associated with the risk of bleeding complications (Odd ratio: 1.011, 95% CI:1.002-1.021, p=0.023). Conclusion: The plasma apixaban level shows a trend of increase with worsening renal function, and an increase in the plasma apixaban level is suggestive of an increased risk of bleeding complications in patients with CKD. Further large-scale prospective studies are needed to evaluate relationship between plasma apixaban level and renal function as well as safety outcome in CKD patients. Moreover, the role of drug level monitoring should be prospectively evaluated for dosage optimization and the minimization of bleeding risks in CKD patients.